PENGARUH PEMBERIAN EKSTRAK BELIMBING WULUH (Averrhoa bilimbi) TERHADAP BERAT RESIDU FORMALIN IKAN TONGKOL (Euthynnus affinis) BERFORMALIN - Aminonatalina Aminonatalina; Emmy Sri Mahreda; Ahmadi Ahmadi; Uripto Trisno Santoso (EnviroScienteae, 2016)
This study aimed to analyze the effects of the concentration and duration of submersion in the extract of ‘belimbing wuluh’ on the decrease of the weight of formaldehyde residue, and also to analyze the concentration and optimum submersion length of time to produce the decrease of the highest weight of formaldehyde residue on the formaldehyde tuna fish. The study used an experimental method. The design used was a completely factorial randomized design (CRD), using two factors: duration of soaking factor (A) and the concentration factor (B) extracts of ‘blimbing wuluh’. Factor (A) was implemented for 15 minutes, 30 minutes, 45 minutes and 60 minutes, while factor (B) was done for 0% (control), 20%, 40%, 60%, 80% and 100%. Based on the experiments, the research showed that prolonged submersion gave significant effects on decreasing the residual formaldehyde, while the extract concentration ‘blimbing wuluh’ gave very significant effect in reducing the residual formaldehyde of tuna fish. For optimum results,  a concentration of 60% with prolonged submersion for 30 minutes  resulted in the reduction of residual formaldehyde percentage of 81.25%, the highest percentage compared with other treatments.